"We need to offer something better to the scholars of the future": Some thoughts on the "Hodgson debate" - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2022)
After the global financial crisis, hopes were high that there would be a pluralisation of the economics discipline and a boost for heterodox economics that challenged dominant economic models. However, mainstream economics once again proved its enormous resilience and the future of alternatives to this mainstream is anything but certain. Geoffrey Hodgson's new book on this issue has sparked fresh discussions about the stunted development of heterodox economics and proposals for possible ways forward. This article will argue that the crucial factor for the future of heterodox economics is not converging on a single unified paradigm or raising the quality of research, but rather gaining access to different kinds of capital, first and foremost professorial positions at universities. Such access is severely restricted under present conditions as a result of epistemological and ontological discrimination. Heterodox economics can only flourish if the epistemic community of economists embraces paradigmatic pluralism as part of their academic culture, or if regulations are put in place to secure access to such capital and so to academic freedom.
Keywords: B50; B51; B52; 330; heterodox economics; pluralism; orthodox economics